2017
DOI: 10.1136/thoraxjnl-2016-208900
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nocturnal actigraphic sleep measures in patients with COPD and their association with daytime physical activity

Abstract: There is a relationship between measures of sleep in patients with COPD and the amount of activity they undertake during the waking day. Identifying groups with specific sleep characteristics may be useful information when designing physical activity-enhancing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 41 publications
0
49
1
3
Order By: Relevance
“…Recently, it was suggested that sleep quality might increase the amount of physical activity the next day and thus have a favorable impact on lifestyle. 25 Moreover, it was previously shown in patients with obesity hypoventilation syndrome that exercise tolerance results increased with NIV and CPAP but more with NIV. 26 Altogether, these findings suggest that the improvements in these groups may have been related to better nocturnal oxygenation and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that sleep quality might increase the amount of physical activity the next day and thus have a favorable impact on lifestyle. 25 Moreover, it was previously shown in patients with obesity hypoventilation syndrome that exercise tolerance results increased with NIV and CPAP but more with NIV. 26 Altogether, these findings suggest that the improvements in these groups may have been related to better nocturnal oxygenation and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Still related to socialenvironmental factors, Arbillaga-Etxarri et al [41] recently observed that dog walking and grandparenting are associated with a higher amount and intensity of physical activity in patients with COPD. In another recent study it was shown that patients with COPD who sleep better (e.g., non-fragmented sleep) are more physically active in the following day [42]. Finally, in a large multicentre randomised controlled trial, Demeyer and coworkers [43] have shown that the amount and intensity of physical activity can be significantly increased in patients with COPD using a 12-week semiautomated telecoaching intervention when compared to the usual care group.…”
Section: Characteristicmentioning
confidence: 97%
“…Importantly, there was a clear correlation between quality of sleep and physical activity. While a casual relation could obviously not be proven, it was however suggested by the fact that days with reduced physical activity were preceded by nights with poor sleep quality [188]. The underlying causes though, remain unclear, with increased work of breathing, associated symptoms or associated hypoxemia (see below) being potential candidates.…”
Section: Sleep Quality and Pulmonary Rehabilitationmentioning
confidence: 99%